Microstructural Evolutions and its Impact on the Corrosion Behaviour of Explosively Welded Al/Cu Bimetal - Mohammad Reza Jandaghi; Abdollah Saboori; Gholamreza Khalaj; Mohammadreza Khanzadeh Ghareh Shiran (Metals, 2020)
In this study, the microstructural evolutions and corrosion resistance of aluminium/copper joint fabricated through explosive welding process have been thoroughly investigated, while stand-off distance was variable. Microstructural analyses demonstrate that, regardless of grain refinement in the welding boundary, increasing the stand-off space is followed by a higher thickness of the localized melting pool. X-Ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDS) analyses recognized the binary intermetallic layers as a combination of Al2Cu and AlCu. Polarization and electrochemical impedance spectroscopy (EIS) corrosion tests revealed that a higher stand-off distance resulted in the increment of corrosion potential, current rate, and concentration gradient at the interface owing to the remarkable kinetic energy of the collision, which impaired corrosion resistance.